2015
DOI: 10.1017/jfm.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive boundary layers over varying topography

Abstract: Diffusive bottom boundary layers can produce upslope flows in a stratified fluid. Accumulating observations suggest that these boundary layers may drive upwelling and mixing in mid-ocean ridge flank canyons. However, most studies of diffusive bottom boundary layers to date have concentrated on constant bottom slopes. We present a study of how diffusive boundary layers interact with various idealized topography, such as changes in bottom slope, slopes with corrugations and isolated sills. We use linear theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Can up-ridge mean flows within canyons be strong enough to maintain stratification without the need for restratification by submesoscale eddies? In calculations with uniform mixing and an infinitely deep rectangular canyon, Dell (2013) found mean flows parallel to the canyon axis that were indeed stronger than predicted by one-dimensional theory, but these flows were oriented largely along isopycnals and thus had little effect on the stratification. We here extend Dell's calculations to the more realistic case with bottomintensified mixing and a canyon that has sloping walls and is embedded in a ridge flank (Fig.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Can up-ridge mean flows within canyons be strong enough to maintain stratification without the need for restratification by submesoscale eddies? In calculations with uniform mixing and an infinitely deep rectangular canyon, Dell (2013) found mean flows parallel to the canyon axis that were indeed stronger than predicted by one-dimensional theory, but these flows were oriented largely along isopycnals and thus had little effect on the stratification. We here extend Dell's calculations to the more realistic case with bottomintensified mixing and a canyon that has sloping walls and is embedded in a ridge flank (Fig.…”
Section: Introductionmentioning
confidence: 76%
“…Boundary layer theory neglects any variations of the flow in the plane of the slope. Such variations can arise if the far-field stratification is not constant (e.g., Phillips et al 1986), if the mixing is inhomogeneous in the plane of the slope (e.g., McDougall 1989), and if there are variations in the slope itself (e.g., Dell and Pratt 2015;Holmes et al 2018). We here focus on the latter case, considering a full mid-ocean ridge (Fig.…”
Section: Mean Flows and Submesoscale Eddies Over Mid-ocean Ridge Flanksmentioning
confidence: 99%
See 1 more Smart Citation
“…We emulate the PGCM solution by using finite differences to solve the time-dependent boundary layer equations (21)-(23) with the local Coriolis parameter f(y) and slope angle u(x, y) at each (x, y) cell of the PGCM grid, which is a sensible approach given that the parameters f(y) and u(x, y) vary on scales larger than the those of the boundary layer solutions (Dell and Pratt 2015). Since these local boundary layer solutions are given in terms of the local slope-normal direction z 0 rather than the true vertical direction z, we project the solution onto the true vertical direction z with the substitution z 0 / z/cosu and linearly interpolate from the projected z levels of the boundary layer solution to the PGCM's local s levels.…”
Section: B Emulator Setupmentioning
confidence: 99%
“…Phillips (1970) examined the importance of these flows to mass transport along a fissure in a geological context while Wunsch (1970) postulated that the boundary layers arising from the motion might play a role in oceanic mixing. More recently, Dell & Pratt (2015) suggested that it could drive upwelling near mid-ocean ridges.…”
Section: Introductionmentioning
confidence: 99%